PEMENUHAN KEBUTUHAN AMUNISI UDARA: SUATU PENDEKATAN TRIPLE HELIX - Besi, Adhe Panggar; Dermawan, Windy; Napitupulu, Heri (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The development of military threats and the global Arms Races trend pose serious challenges for Indonesia. The Indonesian Air Force (TNI AU) needs to be supported by fulfilling the need for air ammunition to improve air defense capabilities in facing the dynamics of these threats. This study aims to analyze the fulfillment of Indonesia's air ammunition needs through a triple helix approach involving interaction between government, industry, and academics. This effort is to strengthen the independence of the national defense industry in the production of air ammunition to meet the needs of the TNI AU. Through the triple helix approach, it is expected to improve the quality of production, innovation, and technological capacity through synergy between these parties. This study uses a qualitative method with data collection through in-depth interviews, documentation studies, and literature studies. This study identifies the strategic role of each actor, where the government acts as a regulator and facilitator and supervisor. The defense industry as an applicator, and academics act as innovators in the research and development of air ammunition technology. This study found that the triple helix approach can realize the independence of the national defense industry and can improve the quality of air ammunition production according to the standards of the TNI AU's needs. This study also concluded that Indonesia is able to increase the competitiveness of its national defense industry through a sustainable collaborative approach in meeting the air ammunition needs of the Indonesian Air Force.